Saluran Pemasaran Tandan Buah Segar Kelapa Sawit Di Desa Kartika Bhakti - Hermansyah, Hermansyah; Neyatri Bandrang, Tirsa; Andriani, Selvi (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2025)
The marketing channel of Fresh Fruit Bunches (FFB) oil palm in Kartika Bhakti Village has a marketing channel, namely (Farmers – Collectors – PKS companies), which affects farmers when selling Fresh Fruit Bunches (FFB) to collectors because the distance of the sales location between oil palm plantations is not far from the place of sale, purchase of unsorted palm oil FFB, loan bonds and subscriptions. So collector traders play a key role as a link between farmers and SMEs, but can also be a source of economic dependence for small farmers. The marketing margin of Rp.964/kg shows the costs and profits taken by marketers in the palm oil distribution chain. Meanwhile, the farmer share of 67% indicates that farmers receive most of the final selling price.